Integrasi Kemaritiman dan Moderasi Agama dalam Materi Ajar Bahasa Arab Berbasis Literasi Digital - Kholiq, Ilham Nur; Mahbub, Mahbub (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Teaching material is the most important part of learning Arabic. It is not just the content of the material but contains maritime values and religious moderation based on digital literacy. Madrasah Aliyah Country 1 Banyuwangi integrates and internalizes these values in order to foster students' cognitive, affective and psychomotor attitudes in the Merdeka curriculum. The aim of this research is to examine policies and describe the Arabic language learning process that integrates maritime values and religious moderation . The research method used is descriptive qualitative case study type. Based on the findings, maritime integration is due to Banyuwangi having good natural potential such as themes related to the beach, and local culture and the integration of religious moderation such as tolerance and harmony. In its application to digital literacy, students use cellphones in learning Arabic, such as improving their ability to read, compile and write information, apart from that, mastering mufradat can be done through various information, increasing focus or concentration and improving the verbal abilities of each individual student